Effects of light intensity and agronomical practices on growth, yield and quality of Sabah Snake Grass (Clinacanthus nutans (Burm.f.) Lindau) - Nasiri, Alireza (2016)
Sabah snake grass (Clinacanthus nutans (Burm. f) Lindau) is a medicinal herb that needs to be investigated since there are a number of claims that this plant is traditionally used as an anti-snake venom, treatment for dysentery, diabetes, fever, regulating menstrual function, relieving pain, anemia, jaundice and setting of fractured bones. In this study, the effect of some environmental factors (light intensity and plant density and nitrogen fertilizer) on physiological and biochemical changes of C. nutans were investigated. Information on the polyphenolic compounds (flavonoids and phenolic acids, saponin and tannin content) of C. nutans and its biological activities are still scarce and such data would be useful to provide information on herbs containing high levels of beneficial components. The first experiment was conducted to determine the effect of different light intensity (200, 395, 600 and 790 JlIIlo1lm2/s) on yield and quality of C. nutans. Effect of different plant densities (30x30 cm, 30x40 cm, 40x40 cm and 40x50 cm) was examined in the second experiment. Third experiment was conducted to evaluate the response of C. nutans to nitrogen (N) fertilizer (0, 100, 150, 200 kg N/ha and chicken dung at 8 ton/ha). All three experiments were conducted based on randomized complete block design with four replications .. The result showed that as light intensity increased carbohydrate content also increased while the protein content decreased for all light intensities. Among all light intensities, the highest total flavonoids content (TF) and total phenolics (TP) was gained under a light intensity of 790 Jlmo1lm2/s with 6.91 mg rutin equivalent /g dry weight and 10.81 mg gallic acid equivalentlg dry weight respectively. The order of TF and TP partitioning under differen~ light levels was: 790 JlIIlo1lm2/~ > 600 umol/rnvs > 395 ~mo1l~2jg > 2~0 umol/m Is. Tannin content also was the highest under 790 umol/m Is, while saponin content was low in this light intensity. Antioxidant activities increased significantly with increasing of TF and TP concentration, and high antioxidant activity, was observed respectively, in C. nutans grown under 790 JlIIlo1lm2/s. The results of HPLC analysis indicated that, except pyrogallol, synthesis and partitioning of orientin, isoorientin, vitexin, isovitexin and rutin were high in plants grown in the open field (790 umol/m' Is). In second experiment both TF and TP, reached to the maximum level in plants with 40x40 cm distance, however there was not a significant difference between 40x40 cm and 40x50 cm distance. The results showed that the highest content of carbohydrate and protein content and also photosynthesis rate was obtained in 40x40 cm distance. Based on the results obtained, orientin, isoorientin and pyrogallol amount were higher under the planting distance of 40x40 cm while the highest amount of vitexin and isovitexin was detected in planting distance of 30x40 cm. Activity of 1,I-Diphenyl-2-picryl-hydrazyl (DPPH) and Ferric Reducing Antioxidant Potential . (FRAP) assay increased at the 40x40 cm planting distance, respectively. With increasing antioxidant power malondyaldehyde (MDA) level decreased for all four . planting densities. In addition, C. nutans extract exhibited the highest anticancer activity in MCF-7 cancer cells with ICso values .of 102.19 and 106.21Ilg/ml for planting distance of 40x40 cm and 40x50 cm respectively. The results of the third experiment showed that, by using an adequate N rate, it was possible to significantly increase and optimize the bioactive compound levels. Highest photosynthesis rate, carbohydrate and protein production were recorded by supplying 150 kg N/ha. At 150 kg N application, the plant contained higher phenolics and flavonoids as well as higher antioxidant activity compared to other nitrogen levels. Application of chicken dung (after "150 kg N) also showed high antioxidant activity. The result also demonstrated that, except rutin, other flavonoids were detected in highest value in 150 kg N treated plants. Cancer cell line (MCF -7) exposed to the extracts showed cytotoxicity with a range of 58.12% for 150 kg N application. These results indicate that the yield and pharmaceutical quality of C. nutans can be enhanced by controlling the agronomic practices.